2016
DOI: 10.1186/s13550-016-0242-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of isoflurane on 18F-FDG uptake in the rat brain: a fully conscious dynamic PET study using motion compensation

Abstract: BackgroundIn preclinical positron emission tomography (PET) studies an anaesthetic is used to ensure that the animal does not move during the scan. However, anaesthesia may have confounding effects on the drug or tracer kinetics under study, and the nature of these effects is usually not known.MethodWe have implemented a protocol for tracking the rigid motion of the head of a fully conscious rat during a PET scan and performing a motion compensated list-mode reconstruction of the data. Using this technique we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 33 publications
4
28
0
2
Order By: Relevance
“…It is possible that we may have observed the increase in FDG uptake, as reported previously 32 and as we observed in electrophysiology experiments, if the animals had been anesthetized during FDG uptake. However, anesthesia is known to produce variability in glucose levels and tracer uptake, relative to the awake condition 39,40 . In particular, isoflurane anesthesia reduces glucose uptake in the cortex, thalamus, basal ganglia, etc., regions in which we wished to study off-target effects 41 .…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that we may have observed the increase in FDG uptake, as reported previously 32 and as we observed in electrophysiology experiments, if the animals had been anesthetized during FDG uptake. However, anesthesia is known to produce variability in glucose levels and tracer uptake, relative to the awake condition 39,40 . In particular, isoflurane anesthesia reduces glucose uptake in the cortex, thalamus, basal ganglia, etc., regions in which we wished to study off-target effects 41 .…”
Section: Discussionmentioning
confidence: 99%
“…One emerging point of concern in preclinical [ 18 F]‐fluoro‐deoxy‐glucose (FDG)‐PET studies is the use of anesthesia during the PET scan. It has been reported that anesthesia can significantly affect the BGluM of rodents (Alkire et al ., ; Shimoji et al ., ; Mizuma et al ., ; Prieto et al ., ; Spangler‐Bickell et al ., ). These studies found that isoflurane anesthesia generally reduces BGluM in cortical regions, but its effect on sub‐cortical regions is unclear.…”
Section: Introductionmentioning
confidence: 97%
“…By comparison to the KX group, the I group showed a relative metabolic increase only in the medial vestibular nucleus. Other studies have also reported relative metabolic increases in the vestibular nucleus of animals anesthetized with isoflurane (Shimoji et al., ; Spangler‐Bickell, De Laat, Fulton, Bormans, & Nuyts, ).…”
Section: Discussionmentioning
confidence: 87%